HUBUNGAN PENGETAHUAN, SIKAP, DUKUNGAN SUAMI, KONTROL PERILAKU, DAN NIAT IBU DENGAN PERILAKU KADARZI IBU BALITA GIZI KURANG - Aulidina Dwi Mustafyani; Trias Mahmudiono (Universitas Airlangga, 2017)
Lack of knowledge and attitude might lead to a state of poor behavior in society. Results of nutritional awareness family (KADARZI) survey in 2015 showed 24.09% families and increased to 24.15% in 2016 of families who not aware of nutrition. The aim of the study was to analyze the relationship between knowledge and intention with mother of children under five malnutrition. This was a cross sectional study with 58 samples selected by simple random sampling. Subject in this study was the mother of malnourished children under five. The data were collected through interview using questionnaires, and analyzed using pearson correlation. Of the five indicators, families who weighing weight every months (74.14%), consume a variety of foods (55.1%), iodized salt (100.0%), exclusive breastfeeding (51.72%), and nutritional supplements (100.0%). Most families were having medium level knowledge (53.4%) and poor knowledge (46.6%). There were association between family income (p = 0.040), knowledge (p = 0.033) and intention (p = 0.048) to the behavior of mother towards KADARZI. While attitude, subjective norm, and perceived behavioral control did not have relationship to the behavior of mother toward KADARZI. Knowledge and intention was related to enactment of KADARZI.